Evaluasi Perhitungan Dimensi Tulangan Balok Terhadap Analisa Struktur Pada R6 Portal As-32 Proyek Pembangunan Ruko Citraland Bagya City Medan - Rosalia Sihombing, Lidya; Nurmaidah, Nurmaidah (Universitas Medan Area, 2019)
In the planning of multi-storey construction buildings need to pay attention to all aspects that affect the structure of the building and consideration of mature, especially if a multi-story building is designed to withstand earthquakes, the structure considerations will affect the planner in determining alternative planning. Multi-storey building planning needs to pay attention to several criteria, including strength criteria, good structural behavior at the stage of the earthquake plan as well as economical aspects. Discussion topics focused on the comparison of reinforcement plan beam dimension to structural analysis. The purpose of this report is to know and control how the calculation of flexural repetition on the beam structure. For solving this problem a case study is provided that provides theoretical information and analysis. Information in the form of data is processed through computer simulation Program Structure Analysis. Above modeling is made, analyzed to obtain results and discussed for calculation of beam reinforcement dimension ratio. The result of calculation obtained from comparison of reinforcement dimension of portal structure of AS-32 port obtained less amount of reinforcement result of calculation from amount of reinforcement used in field with max comparison value 33%, the difference happened because different assumptions or methods in the calculation analysis.